Phân tích so sánh tính chất xốp của vật liệu silica rây phân tử mao quản trung bình có cấu trúc lục lăng SBA-15 và MCM-41 - Sơn và cộng sự, Lê Thanh (Vietnam Journal of Chemistry, 2014)
A study on textural properties of   the SBA-15 and MCM-41 materials was conducted. The SBA-15 material was synthesized using triblock copolymer EO20PO70EO20 (P123)  as template under strong acid conditions while the MCM-41 material was synthesized using  cethyltrimethyl ammonium bromide (CTAB) as template under basic conditions. By employing the characterization techniques of XRD, TEM and physical adsorption of N2 in combination with t-plot, the textural properties of SBA-15 were compared with those of MCM-41. MCM-41 has a hexagonal array of uniform cylindrical pores while SBA-15 is more complex than an array of hexagonally ordered channels. The t-plot provided the evidence that its primary mesopores are accompanied by a certain amount of micropores within mesoporous walls of the main channel. The objective of the present  study is to provide basic information of textural properties of these materials to find out more abut their applications.